DESIGNING WEBSITE-BASED MOBILE APPLICATION USING QUICK SORT AND INSERT SORT METHODS IN ASSIPA DRUG STORE, KARANG ANYAR, SOUTH LAMPUNG - Adytia Ramawan; Yuni Puspita Sari (Prosiding International conference on Information Technology and Business (ICITB), 2020)
The implementation of the data sorting methods were in the form of bubble sort algorithm, insertion sort algorithm, quick sort algorithm, merge sort algorithm, heap sort algorithm, shell sort algorithm, radix sort algorithm, tree sort algorithm, and maximum sort algorithm. Assipa Pharmacy was the drug store which conducted the transactions with more than 100 consumers per day with general purchases (with a green symbol) through a doctor's prescription (with a blue and red circle symbol through the letter K). Assipa Pharmacy had approximately 200 medicinal products with various types of brands. The problem statement of this study was that there was a difficulty on sorting data (e.g., drug products, manufacturers, composition, indications, dosages, drug administration, certain drug interactions) and required a long time in searching this drug data. The objective of this study was to design web-based mobile application using the quick sort and insert sort method in Assipa Drug Store, KarangAnyar, South Lampung. The website-based mobile application was designed on a website containing the data of drug and consisting of a quick sort and insert sort method on the products page so that the data of the drug was able to be accessed through a desktop or mobile (android). Moreover, the prototype software development method and the programming languages were Java, PHP, HTML, and the MySQL database. This software was tested through a black box with 5 components e.g., function and button testing, interface test, loading performance and behavior test, structure and database test, and initiation test and termination.Keywords:Data Ordering, Medicine, Prototype, HTML